Case Report: Synchronous aspirin-induced ileal ulcer and ascending colon adenocarcinoma: diagnostic challenges and pathophysiological insights from an incidental intraoperative finding - Zhao, Zejin; Xiao, Yue; Zhao, Hui; Li, Jian; Liu, Jinlong (Frontiers in Medicine, 2025)
Synchronous gastrointestinal lesions are rare, especially when colon cancer is complicated by non-specific ileal ulcers. This article presents the case of a 70-year-old man who was admitted to the hospital with a colonic space-occupying lesion detected during the physical examination. An unexpected intraoperative finding revealed a synchronous ileal lesion with signs suggestive of malignancy. The patient had no history of inflammatory bowel disease and was on regular low-dose aspirin (100 mg/d) for a long time. Colonoscopy showed a mass in the ascending colon, and biopsy confirmed the diagnosis of moderately differentiated carcinoma. In addition to the ascending colon tumor, an ulcer with focal necrosis and enlarged lymph nodes was observed in the ileum approximately 40 cm from the Bauhin valve, which was suspected to be malignant or heterogeneous. To ensure complete removal of the lesion, a partial resection of the right hemicolon combined with the ileum was performed, followed by bowel reconstruction using a single anastomosis technique. The right upper colon and terminal ileum were resected as a whole, measuring approximately 60 cm in length. Postoperative pathology confirmed the diagnosis of colonic adenocarcinoma (pT3N0M0) and non-specific ulceration of the ileum, while ruling out Crohn’s disease, infection and other potential causes. The combination of the patient’s medical history and the absence of evidence of metastasis suggests that aspirin-associated mucosal injury and distant pro-inflammatory mechanisms related to the tumor may be synergistically pathogenic. The patient’s postoperative recovery was smooth, with no complications. This case emphasizes the importance of comprehensive intraoperative exploration, highlights the key role of multidisciplinary collaboration in differential diagnosis and surgical decision-making, and provides valuable insights for the individualized management of synchronous gastrointestinal lesions.